A Cross Sectional Evaluation of a Shoulder and Elbow Fellowship in a Low to Middle Income Country: Fellows' Perspective - Boskovic, Viseslav-Willy (Division of General Surgery, 2023)
Background: There is a growing trend towards sub specialization and fellowship training in orthopaedic surgery. Data from the United States has shown that over 90% of orthopaedic residents plan to pursue fellowship training and there is a trend in the orthopaedic job market toward seeking fellowship-trained orthopaedic surgeons. Objectives: This study aimed to elucidate graduate perceptions of how undertaking the shoulder and elbow fellowship offered by the Department of Surgery, University of Cape Town (UCT) impacted their professional and personal development and to identify potential means of improving the quality of the programme. Methods: A descriptive, cross-sectional survey analysis was performed using an online questionnaire posing questions related to various aspects of the training programme. Subjects consisted of nine qualified orthopaedic surgeons who had completed the UCT Shoulder and Elbow fellowship. Survey questions were predetermined through discussion and agreement among the researchers. Results: All emails sent drew responses to the survey. An overall good to excellent level of satisfaction with the various aspects of the training program was reported by the fellowship candidates. Post-fellowship increase in arthroscopic and open surgical skill level, as well as understanding of research, was found to be significant. The majority agreed that the fellowship had adequately prepared them for work in their current setting. The candidates strongly agreed that the fellowship enhanced their abilities, when compared to their peers, in pre-operative decision making, intra-operative decision making, formulating ethical judgements, operative surgical skills and teaching ability. Conclusion: The results confirm the positive impact of the fellowship on post-training levels of confidence across clinical, research, decision-making and educational domains by Fellows. The study highlights the benefits of post-graduate fellowship training with the analysis being broadly applicable to similar training programmes globally. It underscores the importance of continuous evaluation of fellowship programmes.